Ways To Effectively Use Chinese Experience In Developing Tourism In Uzbekistan - Miraxmedova, Kamola (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
In the 21st century, tourism is an important part of the world economy, creating sustainable growth, cross-cultural contacts and new jobs, thus benefiting society. China, acting with strategic initiatives since the 1980s, has created a “tourism miracle” in world tourism, that is, it has been able to make major changes in this area. Uzbekistan, having identified tourism as one of the main areas of economic growth, has also been carrying out large-scale reforms in recent years, but much work still needs to be done in this area, which means that Uzbek tourism can still reach even higher heights. This article proposes ways to make the tourism sector more effective by processing and combining the most useful aspects of China's experience in the specific economic, cultural and geographical conditions of Uzbekistan.